Tesseract Based Data Visualization Technique for Monitoring and management of COVID-19 Patients - Nath, Sayantan; Mala, C (PREPARE@u® | IEI Conferences, 2021)
A continuous process of monitoring the clinical condition of COVID patients is proposed in this paper. The coined technique is fundamentally designed on the multi-dimensional data framework architecture. The measuring method of the continuous monitoring process for a greater number of patients with multiple sensors and medical devices in ICUs in a large hospital is very much difficult to manage and control. The regular health-care monitoring systems are mainly designed on the critical parameters of the patients. These constraints are also taken into account to design the key blocks for this framed Tesseract model with other parameters also e.g. number of wards etc. This model would not only help the doctors to check and analyze the medical data of the patients in a multi-dimensional format but also will help the hospital authority to manage and scrutiny the patient’s database efficiently. This technique would be beneficial for both stakeholders of the medical field.